Is it a high time to focus on iron-mediated pathology initiated by COVID-induced inflammation? - Sukhomlin, Tatiana (Acta Biomedica Atenei Parmensis, 2022)
A comment to paper published in the current issue by Duca et al (Acta Biomed 2022; Vol. 93, N. 2: e2022057 - DOI 10.23750/abm.v93i2.12937 - https://mattioli1885journals.com/index.php/actabiomedica/article/view/12937). The paper demonstrated a link between deregulated iron homeostasis and hyperinflammation in nontreated COVID-19 patients. Iron homeostasis links two generally accepted COVID-initiated pathological events: hyperinflammation and abnormal fibrin clotting. Intensive research is needed to look for the ways how to support and recover FeH in COVID infected patients.